THE INFLUENCE OF NATIVE ENGLISH LECTURER IN IMPROVING STUDENTS MOTIVATION IN COMMUNICATION SKILL: (A RESEARCH ON STUDENTS VII SEMESTER AT ENGLISH LANGUAGE AND CULTURE PROGRAM IN DARMA PERSADA UNIVERSITY) - Yoga Pratama; Fridolini Fridolini (English Education Department, 2021)
The development of information and technology has influenced many aspects of life including education. a lot of people start from students in the university and worker already speaking English fluently, but still there are some problem specifically for the students to speak English, university that have English English language programt is looking to find the solution. By hiring native English teacher or leacturer to improve their student’s motivation in English communication skill, the question is can the native English teacher gives the influence to the student. This research made to analyze how well the native English teacher can give the influence to the students especially in Darma Persada University for the students that are majoring in English Literature and in English Department. This research showed whether hired Native English teacher is a good idea or it isn’t. In this study, researcher used aquantitative approach to analyze the influence of native English lecturer in improving students motivation communication skill.. This research was conducted using the experimental method using pre-test and post-test control design.